the Electrical Resistivity Tomography Untuk Identifikasi Akuifer di Daerah Vulkanik (Studi Kasus: Kaliangkrik-Magelang): Electrical Resistivity Tomography Untuk Identifikasi Akuifer di Daerah Vulkanik (Studi Kasus: Kaliangkrik-Magelang) - Winarti, Winarti; Partama, Misdiyanta (ReTII, 2021)
The availability of ground water is one of the pillars of life, and must be preserved. The first step in conserving groundwater is identifying its presence. The area on the volcano’s upper slopes functions as a water catchment, resulting in abundant and high-quality groundwater. The Kaliangrik area, which is located on the slopes of Mount Sumbing, is comprised of volcanic rock. The study’s goal was to identify aquifers on volcanic slopes using the Electrical Resistivity Tomography (ERT) method. ERT measurements were taken over a distance of 500 meters, with electrode spacing of 30 meters, and a total n of 6. The Res2DInv software generates a 2D resistivity cross-section that describes the resistivity value laterally and vertically. Aquifers identified through ERT can serve as a basis for groundwater conservation efforts in water catchment areas. The resistivity cross section results show that the topography of the southeast is lower than that of the northwest. The resistivity range is classified into three categories: low (600 ohm meters), high (600-12,000 ohm meters), and very high (> 12,000 ohm meters). Andesite breccia has a low resistivity value as an aquifer, whereas lava has a high resistivity value. The aquifer is 20-25 meters deep (shallow) and includes a porous aquifer system. The southwest (higher topography) is the source of groundwater, so it must be conserved.